2018
DOI: 10.1155/2018/2012560
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Visual Quality and Corneal Structure after DMEK: Does DMEK Approach Optical Quality of a Healthy Cornea?

Abstract: Purpose To evaluate early changes in visual function and visual quality parameters after Descemet membrane endothelial keratoplasty (DMEK) and to compare the outcomes with healthy controls. Methods Thirteen patients who underwent DMEK and 14 controls were evaluated. All subjects underwent visual function evaluation, including visual acuity under photopic and mesopic lighting conditions and contrast sensitivity (CSV) tests CSV 1000 and Pelli-Robson. Corneal parameters were assessed with Oculus Pentacam. Corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
0
21
2
1
Order By: Relevance
“…A total of seven DMEK studies ( n = 692 eyes) ( 49 , 54 , 56 , 60 , 62 , 68 ), and three “triple DMEK” studies ( n = 275 eyes) reported BCVA at 1–6 months postoperative ( 64 , 65 , 67 ). The mean BCVA following DMEK was 0.50 logMAR (reported by one study), 0.14 (95% CI: 0.10–0.20) logMAR, and 0.07 (95% CI: 0.09–0.22) logMAR at 1-, 3-, and 6-month postoperative, respectively ( Figures 5C,D ), whereas the mean BCVA following “triple DMEK” was 0.19 (95% CI: 0.12–0.29) logMAR, 0.15 (95% CI: 0.11–0.19) logMAR, and 0.19 logMAR (reported by one study) at 1, 3, and 6 months postoperative, respectively ( Figures 5E,F ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven DMEK studies ( n = 692 eyes) ( 49 , 54 , 56 , 60 , 62 , 68 ), and three “triple DMEK” studies ( n = 275 eyes) reported BCVA at 1–6 months postoperative ( 64 , 65 , 67 ). The mean BCVA following DMEK was 0.50 logMAR (reported by one study), 0.14 (95% CI: 0.10–0.20) logMAR, and 0.07 (95% CI: 0.09–0.22) logMAR at 1-, 3-, and 6-month postoperative, respectively ( Figures 5C,D ), whereas the mean BCVA following “triple DMEK” was 0.19 (95% CI: 0.12–0.29) logMAR, 0.15 (95% CI: 0.11–0.19) logMAR, and 0.19 logMAR (reported by one study) at 1, 3, and 6 months postoperative, respectively ( Figures 5E,F ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with Scheimpflug imaging demonstrated increased CD in edematous states following DMEK surgery which decreased as the eyes were followed longitudinally. 21 , 23 , 25 27 To explain the decreased CD in our dehisced DMEK areas, the darker images (decreased CD) on AS-OCT may represent aqueous fluid percolating through the stroma and creating small pockets of fluid (because fluid is seen as dark on AS-OCT, e.g., epithelial bullae). The edematous lamellar separations lead to decreased CD.…”
Section: Discussionmentioning
confidence: 99%
“… 19 CD has previously been studied in DMEK, but these studies were all done with Scheimpflug imaging (i.e., Oculus Pentacam; Oculus, Wetzlar, Germany). 2 , 20 27 Limitations in the Pentacam software do not allow for selection of specific regions of interest for CD measurement. Rather, studied areas are typically confined to four annular zones (0–2 mm, 2–6 mm, 6–10 mm, and 10–12 mm) and four corneal layers (anterior, posterior, central, and total).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the software calculates corneal densitometry (backscattered light) using an add-on tool to the standard software of the Pentacam. 9 The program first identifies the corneal apex, captures 25 images over different meridians, and then analyzes an area with a diameter of 12 mm. Densitometric measurements are presented in grayscale units ranging from 0 (a minimum light scatter and maximum transparency) to 100 (a maximum light scatter and minimum transparency).…”
Section: Methodsmentioning
confidence: 99%